2020
DOI: 10.1177/0003489420952470
|View full text |Cite
|
Sign up to set email alerts
|

Otolaryngology Match 2020-21: Survey of Prospective Applicants in the Setting of COVID-19

Abstract: Objectives: To capture the perspectives of candidates applying for otolaryngology residency positions in the 2020-21 cycle, in the context of disruption caused by the coronavirus disease 2019 (COVID-19) pandemic. Subjects and methods: Candidates planning to apply to the otolaryngology 2020-21 match were invited to complete a cross-sectional online survey. Distribution was via otomatch.com and word of mouth. Descriptive statistics were performed. Results: Of 85 eligible responses (estimated 18.9% of all applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(69 citation statements)
references
References 12 publications
3
65
1
Order By: Relevance
“…With the COVID‐19 pandemic and the limitation of in‐person engagement, the role of social media has become further amplified in 2020. Otolaryngology candidates are less confident in matching and are planning to apply and interview more broadly in the 2020 to 2021 academic year 24 . A majority of program directors express concerns that virtual interviews will impact their ability to assess candidates properly 34 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the COVID‐19 pandemic and the limitation of in‐person engagement, the role of social media has become further amplified in 2020. Otolaryngology candidates are less confident in matching and are planning to apply and interview more broadly in the 2020 to 2021 academic year 24 . A majority of program directors express concerns that virtual interviews will impact their ability to assess candidates properly 34 .…”
Section: Discussionmentioning
confidence: 99%
“…However, from 2017 to 2020, the number of social media users in the United States has grown by nearly 10 million 22 . Coronavirus disease 2019 (COVID‐19) has further amplified the role of social media by disrupting traditional in‐person professional exchanges such as national conferences, trainee job interviews, and away rotations, all of which are virtual for the 2020 to 2021 academic year 23–25 . The objective of this study was to correlate the longitudinal use and popularity of Facebook, Twitter, and Instagram with reputations of otolaryngology residency programs in the United States from 2016 to 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, these means have been previously used to assess general trends among applicants. 4 , 5 As with all survey-based research, this study is limited by potential bias. Inherent risks include capturing only those motivated to respond or a sample not representative of all applicants.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is not yet information on match results by gender, a survey of ENT applicants in 2020 suggested that females may be more negatively affected by virtual interviewing than males. In this survey, 70.0% of female applicants felt less confident about their ability to match because of the switch to virtual interviewing, compared to only 47.1% of male applicants [18]. To continue to promote gender equity, it is imperative that future research seek to determine the reasons behind this difference and find ways to address them.…”
Section: Institutionalized Discrimination In the Virtual Agementioning
confidence: 96%
“…One of the major concerns going into the 2020-2021 interview season was that the decreased cost and increased ease of interviewing, as well as fears that the unusualness of this application cycle would affect candidates' abilities to match, would lead to applicants applying to and interviewing at significantly more programs as backups [18,19]. Preliminary data from the AAMC confirm that surgical programs received an average of 1,045.68 applications for the 2021 match cycle, increased from 887.57 in 2020 [20].…”
Section: Increased Number Of Applications Per Programmentioning
confidence: 99%